PENGARUH PENDIDIKAN, PELATIHAN, DAN PENGALAMAN MENGAJAR TERHADAP PROFESIONALISME DOSEN DI UNIVERSITAS ISLAM JEMBER - Rumartiningsih Rumartiningsih (IKIP PGRI Jember, 2018)
his research is conducted at Islamic University of Jember. The research sample is 30 people, the purpose of this research is 1) to know the influence of simultaneous, partial and dominant influence from education, training and teaching experience to lecturer professionalism at Islamic University of Jember. Variables in this study consist of free variables include education (X1), Training (X2) and Experience teaching (X3); Variable bound by lecturer professionalism (Y). The results showed that simultaneously education, training and teaching experience had a very significant influence on the professionalism of lecturers at the Islamic University of Jember evidenced by the value of Fhitung is 2.504. Partially, education, training and teaching experience have a significant influence on the professionalism of lecturers at the Islamic University of Jember. This is evidenced by the value t arithmetic each independent variable namely: education value of t count equal to 3,073, training t value count 2,456 and experience t teaching value count 4,354. thus it can be said that all partially free variables have a significant influence on lecturer professionalism t value counted 2.957 with significance level 0.007; as well as teaching experience have a dominant influence in influencing professionalism of education, training and teaching experience on lecturer professionalism at Islamic University of Jember.